SYDIR VOROBKEVYCH ON POETICS: THEME, IDEA / СИДІР ВОРОБКЕВИЧ ПРО ПОЕТИКУ: ТЕМА, ІДЕЯ - Tetyana NYKYFORUK (Актуальні питання суспільних наук та історії медицини, 2021)
The purpose of the article. To analyze the scientific literature related to the study of the elements of poetics of poetic works of S. Vorobkevych. To study the author's views on the form